The Moderating Role of Financial Literacy between Herding Behavior and Investment Decisions in Nepalese Mutual Funds - Koirala, Kamal Bahadur; Niraula, Ganesh Prasad (Nepal Journal of Multidisciplinary Research, 2025)
Background: The aim of this research was to examine and explain how financial literacy influences the effect of herding behavior on the investment decisions made by Nepalese mutual fund investors. Financial literacy can play a crucial moderating role in reducing the predominance and negative effects of herding behaviors among Nepalese mutual fund investors. Methods: Data were collected from 386 participants engaged with NEPSE and mutual funds using a convenient sampling method. An explanatory research design with quantitative approach was used. The statistical analysis used both regression models and Structural Equation Modeling (SEM) in R Software to assess the direct, indirect, and interaction effects of herding behavior and financial literacy on investment decision-making. Results: The research found a significant positive link between herding behavior and investor decision-making, a bold positive link between financial literacy and decision-making, and that financial literacy moderated the influence of herding behavior on mutual fund investment decisions. Conclusion: The study concluded that investors, financial advisors, and policymakers should develop better investment strategies and regulations as per the insights gained from this research in order to mitigate the unfavorable effects of investors’ herding behaviors. The study recommends the initiation of training programs, workshops, and seminars to reduce herding behavior by improving the financial knowledge of investors, Novelty/Value: This research fills in the research gap and adds to the existing literature on these important constructs and offers empirical evidence regarding their impacts within the financial markets of Nepal. It is found that focused financial education initiatives can enable Nepalese investors to bridge the knowledge gap, reduce herd behavior, and make rational mutual fund investment decisions.